TIE-2 Signaling Activation by Angiopoietin 2 On Myeloid-Derived Suppressor Cells Promotes Melanoma-Specific T-cell Inhibition - Marguier, Amélie; Laheurte, Caroline; Lecoester, Benoît; Malfroy, Marine; Boullerot, Laura; Renaudin, Adeline; Seffar, Evan; Kumar, Abhishek; Nardin, Charlée; Aubin, François; Adotevi, Olivier (Frontiers in Immunology, 2022)
Myeloid-derived suppressor cells (MDSCs) are a heterogeneous group of immune suppressive cells detected in several human cancers. In this study, we investigated the features and immune suppressive function of a novel subset of monocytic MDSC overexpressing TIE-2 (TIE-2+ M-MDSC), the receptor for the pro-angiogenic factor angiopoietin 2 (ANGPT2). We showed that patients with melanoma exhibited a higher circulating rate of TIE-2+ M-MDSCs, especially in advanced stages as compared to healthy donors. The distribution of the TIE-2+ M-MDSC rate towards the melanoma stage correlated with the serum level of ANGPT2. TIE-2+ M-MDSC from melanoma patients overexpressed immune suppressive molecules such as PD-L1, CD73, TGF-β, and IL-10 suggesting a highly immunosuppressive phenotype. The exposition of these cells to ANGPT2 increased the expression of most of these molecules, mainly Arginase 1. Hence, we observed a profound impairment of melanoma-specific T-cell responses in patients harboring high levels of TIE-2+ M-MDSC along with ANGPT2. This was confirmed by in vitro experiments indicating that the addition of ANGPT2 increased the ability of TIE-2+ M-MDSC to suppress anti-tumor T-cell function. Furthermore, by using TIE-2 kinase-specific inhibitors such as regorafenib or rebastanib, we demonstrated that an active TIE-2 signaling was required for optimal suppressive activity of these cells after ANGPT2 exposition. Collectively, these results support that TIE-2+ M-MDSC/ANGPT2 axis represents a potential immune escape mechanism in melanoma.